A COMPETÊNCIA DELEGADA NA TUTELA DA SAÚDE - Carbone, Diego Cassiano Lorenzoni (Revista da AJURIS, 2013)
THE DELEGATION-OF-JURISDICTION SYSTEM FOR HEALTH-RELATED LAWSUITS RESUMO: O presente trabalho versa sobre a possibilidade e utilidade da instituição, por lei, de competência delegada aos juízes estaduais para julgamento de ações movidas contra a União que envolvam a tutela da saúde. Sustenta, também, a possibilidade de o próprio juiz estadual interpretar ampliativamente a norma do art. 109, § 3º, da Constituição Federal, no ponto que prevê a competência delegada para ações previdenciárias, e elastecer seu alcance para abarcar também ações de tutela da saúde. Por fim, afirma as vantagens da adoção do modelo proposto de competência delegada, em especial no que toca à eficácia do direito fundamental à saúde e à repercussão econômica das decisões proferidas nas demandas de tutela da saúde. PALAVRAS-CHAVE: Tutela da saúde; competência delegada; direito fundamental à saúde; repercussão econômica das decisões judiciais. ABSTRACT: The present paper treats of the possibility and utility of delegating federal jurisdiction to state court judges to judge lawsuits related to the right to health pleaded against the Union. It sustains also the possibility of a state court judge interpreting extensively the rule of article 109, § 3º, of Federal Constitution – at the point it establishes the state court jurisdiction over social welfare-related lawsuits – and enlarge the scope of this rule, to achieve also the health-related lawsuits. Finally, states the benefits of adopting the delegation-of-jurisdiction system as proposed, mainly regarding to the efficacy of the fundamental right to health, and regarding to the economic repercussion of judgments on health-related lawsuits. KEYWORDS: Right to health; delegation of jurisdiction; fundamental right to health; economic repercussion of right-to-health court cases. SUMÁRIO: Introdução;1 A obrigação solidária dos entes federativos; 2 Da possibilidade de ampliação da competência delegada para abarcar hipótese de tutela judicial do direito à saúde; 3 Da utilidade da competência delegada na tutela do direito à saúde; Conclusões; Referências. SUMMARY: Introduction; 1 The solidary responsibility of federated states; 2 About the possibility of enlarge the concept of delegation of jurisdiction system, to achieve also the health-related lawsuits; 3 About the utility of adopting the delegation of jurisdiction system for health-related lawsuits; Conclusions; References.